Translation Methods And Quality Of Noun Phrase In Subtitles Of Kungfu Panda 3 Movie - Muliawan, Anugrah Adi, Dr. Anam Sutopo, S.Pd. M.Hum, Dr. Phil. Dewi Candraningrum, M.Ed (2017)
This research focuses on analyzing the noun phrase found on Kungfu Panda 3 Movie subtitles. The objectives are to identify the translation method of passive noun phrase applied in Kungfu Panda 3 Movie, to describe the accuracy of noun phrase translation on Kungfu Panda 3 Movie, to describe the readability of noun phrase translation on Kungfu Panda 3 Movie, and to describe the acceptability of noun phrase translation on Kungfu Panda 3 Movie. This research applies descriptive qualitative method. The data are the noun phrase found on Kungfu Panda 3 Movie and its translation. The data sources are the subtitle entitled Kungfu Panda 3 Movie and its translation, and the informant or rater. The ways to collect data are by using documentation, questionnaire and in depth Interview. The results of the research show that, firstly, there are seven methods applied to the translation namely word-for-word translation, literal translation, faithful translation, free translation, adaptation translation, semantic translation and communicative translation. From 142 data of noun phrase on Kungfu Panda 3 Movie, there is 1 or 0.7% datum belongs to word-for-word translation, there are 56 or 39.4% data belong to literal translation, there is 1 or 0.7% datum belongs to faithful translation, there is 2 or 1.4% datum belongs to adaptation translation , there are 79 or 54.9% data belong to free translation, there are 2 or 1.4% data belong to semantic translation, and there are 2 or 1.4% data belong to communicative translation. It shows that the most dominant method which is used by the translator is free translation that there are 79 or 54.9% data from 142 data of noun phrase on Kungfu Panda 3 Movie. Secondly, the quality of translation is good. There are 115 or 81% data belong to accurate translation, 4 or 2.8% data belong to less accurate and 23 or 16.2% data belong to unaccurate, there are 121 or 85.2% data belong to acceptable translation, 16 or 11.3% datum belongs to less acceptable and 5 or 3.5% data belong to unacceptable translation and there are 137 or 96.5% data belong to readable translation, 4 or 2.8% data belong to less readable and , 1 or 0.7% data belong to unreadable